Estimasi Produksi Sumber Daya Alam (Produk Tambang) dan Tingkat Kelulusan Sekolah Serta Jumlah Tenaga Kerja Terhadap Pertumbuhan Ekonomi di Indonesia (Studi Kasus Propinsi) - Frances Roi Seston Tampubolon (Jurnal Teknologi Informatika & Komputer)
This research is about estimating the influence of natural resources and school graduation rates and the number of workers on economic growth in Indonesia. The model used is multiple linear regression with one dependent variable and four independent variables. The method used is the OLS (Ordinary Least Square) method, where the estimated parameters of the models are verified by statistical tests. The variables used in this study include the length of time for school graduation, the number of labor (labor), mining products, and PMTDB (formation of gross domestic fixed capital). The results of data processing show that natural resources (mining products) have a positive contribution to Indonesia's economic growth. From the last analysis that the school graduation rate also has a positive relationship to economic growth.